Respuesta :

I'm going to assume you start with

[tex]\dfrac{6^2 - 4 (3 - \sqrt{25})^2}{|4 - 8|}[/tex]

Let's simplify some pieces of this:

[tex]6^2 = 6\times6 = 36[/tex]

[tex]\sqrt{25} = \sqrt{5^2} = 5[/tex]

[tex](3 - \sqrt{25})^2 = (3 - 5)^2 = (-2)^2 = (-2)\times(-2) = 4[/tex]

[tex]|4 - 8| = |-4| = 4[/tex]

So as a first step we can reduce this to

[tex]\dfrac{6^2 - 4 (3 - \sqrt{25})^2}{|4 - 8|} = \dfrac{36-4\times4}4[/tex]

Now,

[tex]36 = 9\times4[/tex]

so every term contains a factor of 4 that we can cancel:

[tex]\dfrac{36-4\times4}4 = \dfrac{9\times4-4\times4}4 = \dfrac{9-4}1 = 9-4 = \boxed{5}[/tex]

as expected.